COVID-19 and Preeclampsia: A Systematic Review of Pathophysiological Interactions - Maria Isabel do Nascimento; Alfredo de Almeida Cunha; Nercélio Falcão Rangel Netto; Raphael Alves dos Santos; Rodrigo Roberto Barroso; Thiago Rodrigues de Carvalho Alves; Wender Emiliano Soares (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective: To review the literature and synthesize evidence on pathophysiological interactions attributed to the simultaneous occurrence of COVID-19 and preeclampsia. Methods: A systematic review was conducted from November (2021) to January (2022) to retrieve observational studies published on the PubMed, LILACS, SciELO Brazil and Google Scholar databases. The search was based on the descriptors [(eclampsia OR preeclampsia) AND (COVID-19)]. Quantitative studies that pointed to pathophysiological interactions were included. Literature reviews, studies with HIV participants, or with clinical approach only were excluded. The selection of studies was standardized and the evaluation was performed by pairs of researchers. Results: In this review, 155 publications were retrieved; 16 met the inclusion criteria. In summary, the physiological expression of angiotensin-converting enzyme-2 (ACE-2) receptors is physiologically increased in pregnant women, especially at the placental site. Studies suggest that the coronavirus binds to ACE-2 to enter the human cell, causing deregulation of the renin-angiotensin-aldosterone system and in the ratio between angiotensin-II and angiotensin-1-7, inducing manifestations suggestive of preeclampsia. Furthermore, the cytokine storm leads to endothelial dysfunction, vasculopathy and thrombus formation, also present in preeclampsia. Conclusion: The studies retrieved in this review suggest that there is a possible overlap of pathophysiological interactions between COVID-19 and preeclampsia, which mainly involve ACE-2 and endothelial dysfunction. Given that preeclampsia courses with progressive clinical and laboratory alterations, a highly quality prenatal care may be able to detect specific clinical and laboratory parameters to differentiate a true preeclampsia superimposed by covid-19, as well as cases with hypertensive manifestations resulting from viral infection.